Engineering bioactive mineralized tumor cells for tumor immunotherapy - Zikun Shen; Yan He; Ren Mo; Dan Shao (Frontiers in Bioengineering and Biotechnology)
IntroductionWhole-cell tumor vaccines are advantageous because of their ability to induce a broad and multifaceted immune response through the presentation of a wide range of tumor antigens, thereby enhancing the ability of the immune system to recognize and target cancerous cells.MethodIn this study, we present a multifunctional vaccine that consists of manganese-mineralized tumor cells and positively charged polymer-immobilized CpG. The Mn2+ and CpG released from the engineered vaccine facilitate the maturation of dendritic cells through the activation of the cGAS-STING and TLR9 pathways, respectively.ResultAs a consequence, the engineered vaccine derived from B16F10 cells exhibited a pronounced tumor-suppressive effect, reducing the tumor volume to approximately one-fifth of that in the control group, and significantly extending survival to day 30 in B16F10 tumor-bearing mice. This superior therapeutic outcome is associated with enhanced activation of dendritic cells, increased infiltration of NK and CD8+ T cells, and increased production of immune cytokines within the tumor microenvironment.DiscussionTogether, our study highlights the immense potential of engineering bioactive mineralized tumor cells to facilitate whole-cell tumor vaccine-based immunotherapy.